Comparison of hindlimb unloading and partial weight suspension models for spaceflight-type condition induced effects on white blood cells - Wilson, Jolaine M (2011)
Animal models are frequently used to assist in the determination of the long- and short-term effects of space flight. The space environment, including microgravity, can impact many physiological and immunological system parameters. It has been found that ground based models of microgravity produce changes in white blood cell counts, which negatively affects immunologic function. As part of the Center of Acute Radiation Research (CARR), we compared the acute effects on white blood cell parameters induced by the more traditionally used animal model of hindlimb unloading (HU) with a recently developed reduced weightbearing analog known as partial weight suspension (PWS). Female ICR mice were either hindlimb unloaded or placed in the PWS system at 16% quadrupedal weightbearing for 4 h, 1, 2, 7 or 10 days, at which point complete blood counts were obtained. Control animals (jacketed and non-jacketed) were exposed to identical conditions without reduced weightbearing. Results indicate that significant changes in total white blood cell (WBC), neutrophil, lymphocyte, monocyte and eosinophil counts were observed within the first 2 days of exposure to each system. These differences in blood cell counts normalized by day 7 in both systems. The results of these studies indicate that there are some statistically significant changes observed in the blood cell counts for animals exposed to both the PWS and HU simulated microgravity systems.